PENERAPAN LESSON STUDY DENGAN MENGGUNAKAN MEDIA WORDWALL DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MATEMATIKA KELAS 6 - Miyen Sapitri; Hikma Dinti Arsya Perdana; Dwi Aria Nopela; Weny Safitri; Wenni Anjarsari; Neza Agusdianita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to implement the application of lesson study using Wordwall media in improving the quality of mathematics learning for grade 6 students. Learning methods in elementary schools are often still teacher-centred, so students tend to memorize without understanding the context. Lesson study is implemented through four stages: planning (plan), implementation (do), observation (see), and reflection (act). The research used a qualitative approach with a case study type, involving 10 grade 6 students as subjects. At the planning stage, the teacher prepares a Wordwall-based learning tool. The do stage involves implementing interactive learning. Observation (see) is carried out to observe student activities, while the reflection (action) stage is used to understand and improve learning strategies. The research results show a significant increase in students' understanding of mathematical concepts, which is reflected in the average score which continues to increase in each cycle. Apart from that, students' active participation in discussions and collaboration has also increased. Implementing Wordwall helps create a more creative and innovative learning atmosphere, so that students are more motivated to learn. Thus, Lesson Study based on Wordwall media is effective in improving the quality of mathematics learning, both in terms of understanding concepts and active student involvement. Keywords: lesson study; Wordwall media; learning quality; mathematics; collaborative learning.